Comparative evaluation of aluminum and stainless steel dissimilar welded joints. (2020) - Singh, Prem; Deepak, Dharmpal; Brar, Gurinder Singh
Abstract: Today's need of lightweight and fuel efficient vehicles in automobile triggers the researchers to develop light weight structures through hybrid or dissimilar welding joints. Dissimilar weld of aluminum and stainless steel offers promising solution in this direction. Many researchers have tried different techniques to produce dissimilar aluminum stainless steel weld using existing commercialized techniques like MIG welding and friction stir welding. In this communication effort have been made to make aluminum stainless steel dissimilar weld with newly friction crush welding technique and weld compression was made with the other techniques available in literature base on micro structural studies. The result shows FCW and FSW weld having good diffusion and inter-looking between dissimilar metals as compared to MIG welding technique.